Kenaf Cellulose Supported Highly Active Poly(Amidoxime) Palladium Complex as a Reusable Heterogeneous Catalyst For Allylic Arylation Reactions - Mandal, Bablu Hira; Sarkar, Shaheen M.; Lutfor, M. R.; Mohd Hasbi, Ab. Rahim (UTM Press, 2016)
A highly active kenaf cellulose supported poly(amidoxime) palladium catalyst was synthesized and characterized with FTIR, UV-Vis, FESEM, XPS and TEM analyses. The catalyst (65 mol ppm to 6.5 mol ppm) was found to promote efficiently the allylic arylation of allylic ester with sodium tetraarylborates in ethanol at 60 °C temperature. Outstanding yields of the corresponding products as well as significant reusability of the catalyst were obtained. The total turnover number (TON) and frequency (TOF) were 144615 and 9641 h–1 respectively.